Portrait of Community Mapping Stages Through Zoning System on Management of Teluk Cenderawasih National Park, West Papua - Fatem, Sepus; Laar, Jim Van (Indian Forester, 2012)
This paper is part of the internship program including field work and desk work in Teluk Cenderawasih National Park office, Manokwari West Papua from November 2009 to February 2010. Field work was conducted to learn how local peoples are involved in zoning stages. This study reveals that the zoning system in Teluk Cenderawasih National Park is known as "community based zoning". There are 12 stages in building zoning in the community mapping process. There are 3260 households which are spread over 64 villages around the national park. Accommodating people’s desires, livelihoods as well as traditional taboos is obligatory. For this reason, zoning was built as one approach in this national park. There are 6 zones as a result from zoning process it self. On the other hand, local people are involved in the whole process not have meaning that there going bail for sustainable way to extract resources by them. In fact, conflict on resources extraction is still going on. In addition, poverty is main in this national park. It has had a big influence on the management of the resources. One pathway to reduce poverty is by economic alternative incentives which will ensure sustainable conservation efforts.